Pengaruh Tingkat Pendidikan dan Pertumbuhan Ekonomi Terhadap Tingkat Kemiskinan di Kabupaten Padang Pariaman - Saputra, Ariski; Vrista, Yuhendri Leo (Jurnal Salingka Nagari, 2024)
The purpose of this study is to examine how economic growth and educational level affect poverty level in Padang Pariaman Regency. This study use causal associative research method. The Central Statistics Agency (BPS) provides the secondary data that is used. Multiple linear regression is used as a data analysis technique. The study's findings show that poverty levels in Padang Pariaman Regency are significantly impacted by economic growth and educational level. Reducing poverty in the area is mostly dependent on expanding educational opportunities and quality as well as inclusive economic growth. In order to promote sustainable economic growth and boost investment in the education sector, this report offers policy recommendations to local governments.